The Effectiveness Of Using Digital Comics Media In The Teaching Of Reading To The Seventh Grade Students Of 172 Junior High School Jakartain The Academic Year 2025/2026 - Mutmainah Mutmainah; Hersulastuti Hersulastuti; Purwo Haryono (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
The issues discussed in this research were: (1) How was the reading ability of grade VII students of SMP Negeri 172 Jakarta before the implementation of digital comic media, (2) How was the reading ability of grade VII students of SMP Negeri 172 Jakarta after the implementation of digital comic media, (3) Whether there was a significant difference in reading ability between the group taught using digital comic media and the group that used conventional learning media, and (4) How effective was the application of digital comic media on the reading ability of grade VII students of SMP Negeri 172 Jakarta in the academic year 2025/2026. The research employed a quantitative approach using a Quasi-Experimental Design with Pre-test and Post-test Control Group Design. The population of this research was the seventh-grade students of SMP Negeri 172 Jakarta, totaling 288 students across eight classes. The sample was selected through cluster random sampling, consisting of Class VII-1 as the Experimental Class and Class VII-2 as the Control Class, with 36 students in each class. The instrument used to collect data was a multiple-choice reading test of 50 items administered as both pre-test and post-test, focusing on recount text comprehension in accordance with the Kurikulum Merdeka framework. The experimental class was taught using Digital Comics media designed through Google Chrome and Canva, while the control class was taught using conventional lecture methods with textbooks. The normality of data was verified through the Shapiro-Wilk test, and hypothesis testing was conducted using the Independent Samples t-Test through SPSS. Based on the analysis of data, it can be concluded that: (1) Before the implementation of digital comic media, the mean score of the experimental class in the pre-test was 58.94, indicating that students' reading ability was below the Minimum Mastery Score (KKM) of 80; (2) After the implementation of digital comic media, the mean score of the experimental class in the post-test increased substantially to 84.72, representing a 43.72% improvement and surpassing the KKM, whereas the control class only reached a mean post-test score of 68.25, reflecting a moderate improvement of 20.96%; (3) The result of the Independent Samples t-Test showed a Sig. (2-tailed) value of 0.000, which is lower than the significance level of 0.05, indicating that there was a statistically significant difference in reading ability between the experimental and control classes; (4) Digital comic media was proven to be highly effective in improving the reading comprehension of seventh-grade students of SMP Negeri 172 Jakarta, as the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted.